Beliefs and barriers of COVID-19 vaccination hesitancy among Sudanese healthcare workers in Sudan: A cross sectional study - Mohamed H. Elbadawi; Lina S. Altayib; Anmar Birier Gadallah Birier; Laila E. Ali; Elfatih A. Hasabo; Mariam Alazraa M. Esmaeel; Osman K. Elmahi; Group of collaborators (Taylor & Francis Group, 2022)
Vaccine hesitancy is one of the major global health impedances. Due to the unprecedented developing rate, the COVID-19 vaccine engendered a high level of hesitancy worldwide. The aim of this study is to assess hesitancy of COVID-19 vaccine among healthcare workers in Sudan. An online-based cross-sectional survey was conducted in Sudan between May and June 2021 using conventional sampling. An anonymous online questionnaire was distributed to healthcare workers (HCW) through different social media platforms and 930 healthcare workers agreed to participate. Data were cleaned in excel sheet and then statistically analyzed using R software version 4.0.2. Of total participants, 67.3% of them were females. Over three-fifths of the study participants agreed that COVID-19 vaccine is important and should be mandatory. A total of 570 (61.3%) agreed that COVID-19 vaccines are safe, whilst 584 (62.8%) had concerns regarding side effects of the vaccine and 533 (57.3%) believe insufficient trials were conducted. A total of 375 (40.3%) accept vaccination absolutely, while 292 (31.4%) accept with some hesitation and only 48 (5.2%) refuse absolutely. Insufficient information about side effects (42.6%) and the vaccine (39.9%) were the most common concerns regarding COVID-19 vaccination. Majority of Sudanese healthcare workers believed that COVID-19 vaccination should be mandatory. A high reliance on social media was observed among healthcare workers in Sudan for information on the COVID-19 pandemic.